2023
DOI: 10.3389/feart.2022.1023578
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of fracture density in a gas reservoir using robust computational approaches

Abstract: One of the challenges that reservoir engineers, drilling engineers, and geoscientists face in the oil and gas industry is determining the fracture density (FVDC) of reservoir rock. This critical parameter is valuable because its presence in oil and gas reservoirs boosts productivity and is pivotal for reservoir management, operation, and ultimately energy management. This valuable parameter is determined by some expensive operations such as FMI logs and core analysis techniques. As a result, this paper attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 83 publications
(86 reference statements)
0
0
0
Order By: Relevance
“…Recent studies have demonstrated the potential of machine learning techniques to estimate discrete fracture properties from well logs. These studies have made significant strides in fracture prediction, utilizing various machine learning algorithms and datasets (Boadu 1998;Ince 2004;Sarkheil et al 2009;Ja'fari et al 2012;Zazoun 2013;Nouri-Taleghani et al 2015;Li et al 2018;Bhattacharya and Mishra 2018;Rajabi et al 2021;Tabasi et al 2022;Pei and Zhang 2022;Delavar 2022;Gao et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the potential of machine learning techniques to estimate discrete fracture properties from well logs. These studies have made significant strides in fracture prediction, utilizing various machine learning algorithms and datasets (Boadu 1998;Ince 2004;Sarkheil et al 2009;Ja'fari et al 2012;Zazoun 2013;Nouri-Taleghani et al 2015;Li et al 2018;Bhattacharya and Mishra 2018;Rajabi et al 2021;Tabasi et al 2022;Pei and Zhang 2022;Delavar 2022;Gao et al 2023).…”
Section: Introductionmentioning
confidence: 99%